The Use of Electrophoresis for the Study of Saliva Involvement in Ingestive Behavior - Lamy, E (2015)
Whole saliva contains a wide variety of proteins with diverse functions, namely proteins which participate in teeth and oral tissues protection, as well as proteins related to ingestive and digestive processes. Several studies, in animals and humans, present evidences that saliva is involved in ingestive behavior. The link between saliva composition and oral perception is increasingly reported. Several studies report that oral sensations, such as astringency, result from interaction between food constituents (e.g. polyphenols) and salivary proteins. Moreover, the involvement of saliva in taste sensitivity has been also considered and an example was the correlation established between taste dysfunction and reduced levels of salivary carbonic anhydrase VI. More recently, studies presented evidences that protein saliva composition is also associated to fat perception and liking, as well as to sensitivity for the bitter taste of 6-n-propylthiouracil (PROP) and caffeine. Besides the involvement of saliva in oral perception, which can greatly influence food choices, the influence of this fluid in ingestive behavior can also be considered by the role of certain salivary proteins in digestive processes or even in the regulation of energy intake: for example, leptin and ghrelin, which are respectively involved in satiety and appetite, are present in salivary secretion. Electrophoresis has been applied for salivary protein separation for years and progresses have been made until now. Several studies report salivary protein separation according to their mass, isoelectric point and both parameters (two-dimensional electrophoresis – 2D), both for human and animal saliva. The application of electrophoresis technique to saliva samples, together with advances in mass spectrometry, for protein identification, resulted in an increased interest in this biological fluid as a source of biomarkers. In fact, saliva collection has the great advantage of being relatively easy, cheap and noninvasive to perform, presenting proteins also existent in other body fluids such as blood. Electrophoresis has also the potential of being used in formalin-fixed and paraffin-embedded tissue samples. This possibility has the great advantage of allowing access to already acquired tissue samples which can be readily correlated with histological parameters. Moreover, it provides access to tissue that would be either difficult to collect prospectively in a timely manner or are unlikely to be available as fresh samples. For salivary composition analysis it may have the potential of allowing the study of individual salivary glands composition, even in situations where no individualized glandular saliva collection was possible. As such, this may have the potential of aiding in the comprehension of salivary gland regulation and different contribution for total salivary composition. This chapter gives an overview of the use of electrophoresis in studies about the involvement of saliva in ingestive behavior. Studies about salivary protein composition in oral sensations and taste sensitivity will be reviewed. The particularities in the use of electrophoresis in saliva samples will be discussed, as well as the advantages and limitations of the technique for the analysis of this body fluid. Moreover, the promising use of electrophoresis of paraffin-embeded tissues for the study of saliva will be proposed. Finally, the major limitations in the electrophoretic study of salivary proteins, such as the presence of high abundant proteins (impairing the study of scarce ones), the high content of mucins, the high proteolitic activity, among others, will be critically revised based on our experience.